SEXUAL VIOLENCE AGAINST WOMEN: MYTH VERSUS JUSTICE FOR VICTIMS - Atikah Rahmi (Proceeding International Seminar of Islamic Studies, 2023)
The cases of sexual violence against women continue to show a significant increase. Violence that occurs is essentially a manifestation of gender injustice, due to unequal relations. Women are humiliated and deprived of their rights. Victims do not only experience physical violence, but also psychological, social violence in the form of ostracism, isolation and social disgrace due to the myths attached to women. Revictimization, even criminalization, is like a bitter pill that victims of sexual violence experience when expressing their suffering. This paper tries to uncover the myth of sexual violence against women which causes injustice to victims, through normative research by collecting literature and materials from the media and supported by the principle of essential justice and mub is a method that is initiated by the Indonesian Women's Ulema Congress (KUPI) as well as personal experience in handling cases of sexual violence. Based on this research, the myths of sexual violence are considered as if they are just normal occurrences and not crimes. Victims should have access to justice because the impact of the violence they experienced was very sad and prolonged.